The Case of the Negative Nominal Interest Rates: New Estimates of the Term Structure of Interest Rates during the Great Depression - Cecchetti, Stephen G. (Journal of Political Economy, 1988)
Throughout the 1930s and early 1940s, U.S. Treasury bonds and notes appeared to have negative nominal yields as they approached maturity. But negative nominal interest rates are impossible in a world in which one can always hold cash. The resolution to this puzzle is that Treasury securities, in addition to making coupon payments, gave the owner the right to buy a new security on a future date. This paper describes the institutional environment that led to the apparent negative nominal interest rates; develops a method for valuing the "exchange privilege"; and computes accurate measures of the yield to the coupon-bearing component of these composite bond/options. Copyright 1988 by University of Chicago Press.